USING COMPUTER AND ONLINE TECHNOLOGIES IN TEACHING ENGLISH - Aminjonova Mohinur G’ayratjon qizi; Ma’murova Navruza Sherzodbek qizi; Ahmedova Matlubaxon Ibragimjonovna (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Anotation: In today’s digital age, the role of computer and online technologies has become increasingly vital in the realm of education. English language teaching, in particular, has witnessed a paradigm shift with the integration of these technologies. This article aims to explore the various ways in which computer and online technologies can be effectively utilized in teaching English, and the benefits they offer to both educators and students. using computer and online technologies in teaching English has become an integral part of language education. In today’s digital age, incorporating technology into English language instruction has proven to be an effective way to engage students and enhance their learning experience. This article will explore the benefits of using computer and online technologies in teaching English, along with practical strategies for implementation.